Development of risk management framework for the construction industry in yemen - Rami Abdullah, Ali Ba Hamid (2023)
Yemen is one of the developing poorest economies in the world, yet it has seen extraordinary growth in construction over the last few decades. The construction sector is considered an important sector in developing economies and contributes significantly to the improvement of the economic growth of any country, particularly in developing countries like Yemen. Construction projects regularly experience a high level of uncertainty due to its Complexity, which definitely exposes them to risks that result a negative impact on the project's objectives. Given developing countries' resource constraints compared to developed countries, it is critical to accomplish construction projects on schedule, within budget, and with the highest possible quality. Thus, risk management is a critical component of the construction industry's decision-making process, as it determines the success or failure of construction projects. The absence of application and understanding of risk management leads to poor construction project performance particularly in developing countries. Risk management in construction projects in Yemen is under-researched compared to developed and developing countries, and lacking a suitable risk management framework. Hence, the main objective of this research is to develop a risk management framework in order to improve the performance of construction projects in Yemen. In order to achieve the research objectives, a mixed-method approach was used, which included semi-structured interviews and questionnaires with participants in a construction project in Yemen. Through an extensive literature review, 56 risk factors affecting construction projects in developing countries from43 studies were identified and categorized. Semi-structured interviews with construction experts in Yemen were conducted and 48 risk factors related to the Yemeni construction projects have been identified. A questionnaire survey utilizing a nonprobability sampling method using a five-point scale was carried out among the construction sector in Yemen to identify the most significant risk factors based on the likelihood of occurrence and impact on the objectives of projects, and to evaluate the current practice and knowledge of risk management in construction projects in Yemen,. 174 responses were completed and collected from the public and private sectors. 17 critical risks were identified using the mean, the relative important index method, and risk acceptability matrix analysis. War and political instability, inflation, and exchange rate fluctuations are identified as the most significant risks. Most of the risks are allocated to the contractor or shared between owner and contractor. The current knowledge and practice of the construction projects in Yemen have been evaluated. The results also show that risk management is not implemented in most projects, the majority of participants in construction don’t have adequate knowledge of risk management, and risk management does not apply systematically in construction projects. Based on the findings from the literature reviews, and data analysis a risk management framework has been developed to be served as a guideline for managing risks in construction projects in Yemen and developing countries. The framework was developed based on the principles including developing the existing frameworks; utilizing risk management tools that have been implemented successfully in other countries. The framework has provided incorporated techniques for risk management that is based on well-defined principles. The developed framework has validated using a semi-structured interview with 16 Yemeni construction experts. Experts’ feedback demonstrates that the developed framework is comprehensive and compatible with the Yemen environment, and does not involve complicated processes. This study will serve as a guideline for participants in construction projects in Yemen to improve the performance of construction projects.